RANCANG BANGUN ANTENA BROADBAND ENAM CABANG SALURAN DENGAN METODE BINOMIAL CELAH KAPASITIF TUNGGAL - Safwan; Syahrial; Rizal Munadi (J-Innovation, 2016)
In general, only one antenna is used for one application. To streamline the use of an antenna, a broadband antenna can be utilized for various applications. One broadband antenna suitable for various applications are broadband antennas six branches of the plate with a single capacitive gap binomial method. This antenna works in the frequency range 0.81 GHz - 3 GHz, which has a bandwidth of 2.19 GHz with a VSWR ≤ 1.5. This antenna has a dielectric antenna different. Dielectric antenna using materials from household waste such as plastic, paper, stereofoam, and others. It became one of the benefits is because the antenna is able to utilize waste materials for the application of technology. This antenna is relatively large dimensions so that the antenna is suitable for use in the transmission system and not be used as a suitable handset. Applications that can use this antenna including GSM 1900, Wifi 2.4 GHz, amateur radio, and more. This antenna uses a binomial method and a single capacitive gap as a method of widening the bandwidth. Binomial method is used to make the antenna impedance into tiers binomial pointless to shrink the transition effect antenna impedance of each level. slit method serves as a single capacitive impedance value improvements that will affect to the bandwidth of the antenna.